Legal Effectiveness and Social Adoption of Digital Public Services: An Analysis of Law No. 25 of 2009 and Mobile JKN Implementation in Primary Healthcare - Fithri, Annisa; Daipon, Dahyul (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2025)
The effectiveness of Law Number 25 of 2009 on Public Services in improving services at the Tigo Baleh Community Health Center (Puskesmas) through the implementation of a digital system, specifically the Mobile JKN application. While designed to enhance efficiency and reduce queues with online registration, this research reveals a gap between expectations and reality. The method used in this research is field research, and the data ushed are in the form of primary data were collected through interviews and direct observation of service users and Puskesmas staff, supplemented by secondary data from relevant literature and documents. Qualitative data analisis indicates low Mobile JKN adoption stems from several factors, including a lack of public understanding of the application and insufficient socialization. Furthermore, the study identifies obstacles in implementing the principles of public service as stipulated in Law No. 25 of 2009, particularly regarding participatory principles and transparency as well as the principles of speed, simplicity, and accessibility. A review of Fiqh Siyasah reinforces these findings, highlighting the unmet principle of justice and utility in its application in service delivery. In conclusion, the effectiveness of Law No. 25 of 2009 in improving public services at the Tigo Baleh Puskesmas through digital systems requires improvement. This study recommends a more comprehensive strategy to enhance community digital literacy, simplify application usage, and ensure optimal implementation of public service principles for more effective and efficient healthcare services.